2021
DOI: 10.3389/fcell.2021.793820
|View full text |Cite
|
Sign up to set email alerts
|

Histologically Confirmed Recellularization is a Key Factor that Affects Meniscal Healing in Immature and Mature Meniscal Tears

Abstract: Healing outcomes of meniscal repair are better in younger than in older. However, exact mechanisms underlying superior healing potential in younger remain unclear from a histological perspective. This study included 24 immature rabbits and 24 mature rabbits. Tears were created in the anterior horn of medial meniscus of right knee in each rabbit. Animals were sacrificed at 1, 3, 6, and 12 weeks postoperatively. We performed macroscopic and histological evaluations of post-meniscal repair specimens. Cells were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…A previous study has demonstrated that apparent cell apoptosis was observed at the tear interface in an adult rabbit meniscal tear model. 35 In the present study, the apoptosis index around the tear interface was evaluated, showing that meniscal tears treated with hyaluronidase and TGF-β3 had the lowest apoptosis index compared with the control group. Moreover, the superior repair and integration of meniscal tears after hyaluronidase and TGF-β3 treatment decreased the degradation of cartilage in the MFC and MTP.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…A previous study has demonstrated that apparent cell apoptosis was observed at the tear interface in an adult rabbit meniscal tear model. 35 In the present study, the apoptosis index around the tear interface was evaluated, showing that meniscal tears treated with hyaluronidase and TGF-β3 had the lowest apoptosis index compared with the control group. Moreover, the superior repair and integration of meniscal tears after hyaluronidase and TGF-β3 treatment decreased the degradation of cartilage in the MFC and MTP.…”
Section: Discussionmentioning
confidence: 75%
“…3,16 Second, cellularity decreases significantly with maturity. 35 Third, the mechanical property and intrinsic fiber arrangement are enhanced with maturity. For instance, with the maturity of the meniscus after birth, the size and density of collagen bundles increase significantly, and the deposition of the extracellular matrix including collagen and proteoglycans increases, thus enhancing mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations